The regulation of MMP targeting to invadopodia during cancer metastasis - Jacob, Abitha; Prekeris, Rytis (Frontiers in Cell and Developmental Biology, 2015)
The dissemination of cancer cells from the primary tumor to a distant site, known as metastasis, is the main cause of mortality in cancer patients. Metastasis is a very complex cellular process that involves many steps, including the breaching of the basement membrane to allow the movement of cells through tissues. The basement membrane breach occurs via highly regulated and localized remodeling of the extracellular matrix (ECM), which is mediated by formation of structures, known as invadopodia, and targeted secretion of matrix metalloproteinases (MMPs). Recently, invadopodia have emerged as key cellular structures that regulate the metastasis of many cancers. Furthermore, targeting of various cytoskeletal modulators and MMPs has been shown to play a major role in regulating invadopodia function. Here, we highlight recent findings regarding the regulation of protein targeting during invadopodia formation and function.